Pengaruh Problematika Keluarga Terhadap Kepribadian Remaja Di Kelurahan Sukaraja Kota Bengkulu - Asiyah Asiyah (At-Ta'lim : Media Informasi Pendidikan Islam, 2015)
This study aims to determine whether there is influence between the problems of the family of the personality of young people in the village Sukaraja town of Bengkulu. Quantitative methods used in this study with participants numbering 25 adolescents aged 12-22 years. Engineering analysis using Pearson product moment correlation. The results showed a significant difference between the problems of the family of the personality of young people in the village Sukaraja Bengkulu City.